The tumor immune microenvironment: implications for cancer immunotherapy, treatment strategies, and monitoring approaches - Racacho, Kelsey Jane; Shiau, Ya-Ping; Villa, Rodolfo; Mahri, Sohaib; Tang, Menghuan; Lin, Tzu-Yin; Li, Yuanpei (Frontiers in Immunology, 2025)
The tumor immune microenvironment (TIME) plays a pivotal role in cancer progression, detection, and response to cancer treatments. Current knowledge of the diverse and dynamic cellular components of the TIME underscores how the immune landscape evolves in response to immunotherapy. This review highlights the importance of understanding the TIME for advancing cancer immunotherapy by integrating insights from basic biology and clinical practice with recent advances in science and technology, paving the way for more personalized cancer therapies through modern medical innovations. The cellular and molecular compositions of the TIME and the cellular interactions will be explored. Next, we summarize how the TIME is shaped by immune activation and suppression through various mechanisms of action. Immunotherapies designed to enhance host immune function are discussed in detail to visualize and quantify cellular dynamics within the TIME once treated with immunotherapy. In particular, the integration of artificial intelligence (AI) has significantly enhanced early cancer detection and diagnostics by analyzing patient samples with greater precision. The topics are structured to explore core principles, immune activation and suppression, imaging methods, current and emerging therapies, and the broader influence of the TIME on diagnosis, monitoring, and treatment strategies.